2015
DOI: 10.1039/c5ra03191e
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate removal by a nano-biosorbent from the synthetic and real (Persian Gulf) water samples

Abstract: The NZVI has been synthesized and immobilized on the ostrich bone waste with high chemical stability to uptake P ions from (Persian Gulf) water. XRD results confirmed the presence of Fe3(PO4)2·8H2O on the B-HNO3-NZVI-P.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…The successful chemical modification of the filter paper by NaOH and NZVI was confirmed by FT-IR spectroscopy (Figure A), in which a broad absorption band at 3250–3500 cm –1 decreased and the bands corresponding to aliphatic bond of the organic support (cellulose fiber) at 2916 and 2854 cm –1 were reduced in the FP–OH–NZVI sample compared to the pristine \filter paper. The additional manifestation of a peak at 802 cm –1 after the NaOH/NZVI treatment was ascribed to Fe(0). , The peaks at 709 and 447 cm –1 can be ascribed to Fe–O stretching vibrations …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The successful chemical modification of the filter paper by NaOH and NZVI was confirmed by FT-IR spectroscopy (Figure A), in which a broad absorption band at 3250–3500 cm –1 decreased and the bands corresponding to aliphatic bond of the organic support (cellulose fiber) at 2916 and 2854 cm –1 were reduced in the FP–OH–NZVI sample compared to the pristine \filter paper. The additional manifestation of a peak at 802 cm –1 after the NaOH/NZVI treatment was ascribed to Fe(0). , The peaks at 709 and 447 cm –1 can be ascribed to Fe–O stretching vibrations …”
Section: Resultsmentioning
confidence: 99%
“…23,24 The peaks at 709 and 447 cm −1 can be ascribed to Fe−O stretching vibrations. 25 The structure of the unmodified filter paper and FP−OH− NZVI were also characterized by XRD (Figure 1B). For the filter paper, the diffraction peaks occur at 15.1, 16.8, and 22.5°, equivalent to the cellulose crystalline phase.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Furthermore, a low n value indicates the existence of a high proportion of high-energy active sites. 25 The values of 1/n were between 0 and 1, which indicated that adsorption was favorable. According to Figures 11 and 12, Freundlich isotherms better explain the adsorption of Hg(II) than…”
Section: Adsorption Isothermsmentioning
confidence: 97%
“…(Bio)sorbent-mediated adsorption is a widely used method for remediating eutrophic waters. Several chemical materials such as Bephos™ (Zamparas et al 2013), Al 2 O 3 (Genz et al 2004), zeolite (Gibbs and Özkundakci 2010), and iron compounds (Deppe and Benndorf 2002;Chen et al 2016), as well as biomaterials such as sawdust (Pantano et al 2017), biochar (Cai et al 2017), corn straw (Wang et al 2016a), and ostrich bone waste (Arshadi et al 2015) have been investigated. Nano-and magnetic sorbents not only are efficient for P-removal but also can reclaim P from aqueous solutions (Cai et al 2017).…”
Section: Introductionmentioning
confidence: 99%